PENGGUNAAN FACEBOOK TERHADAP PESERTA DIDIK SEBAGAI MEDIA PEMBELAJARAN KE-II - Guitari, Melna; Windiastari, Dinda (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Revolution of Industry 4.0 is a revolution where information can be shared by using technology. Nowdays, we have already used this technology indirectly. Such as, we use non-cash to pay some transaction, or we can use mobile application to send money. And as a teacher, he/she also must follow this technology in education program. A teacher must do a change. Not only in how a teacher teachs but must know what purpose the concept of education itself. So,the students can face all challenges in this era. The one example of technologies is Facebook. Teacher can use it in teaching. So that, Facebook is as learning media. Facebook can be applied by students to access information from teacher. Teacher can use facebook to share the subject, the test, the schedule or to see students’ activity. By using facebook, hopely a teacher can manage them well. If the discussion in the class has not finished yet, teacher can discuss it again on the wall of facebook. And all students can see them.